A new candling procedure for thick and opaque eggs and its application to avian conservation management. Issue 2 (7th September 2022) - Hall, Clancy A.; Potvin, Dominique A.; Conroy, Gabriel C.
Abstract: The ability to monitor developing avian embryos and their associated vascular system via candling enables the application of important reproductive management techniques. Egg candling facilitates the confirmation of egg viability throughout the incubation process and identification of a precise position on a vein for the safe extraction of blood. Blood samples may then be analysed to retrieve vital health and genetic information to assist in conservation management. However, the thick or opaque egg shell characteristics of some avian species prevents the observation of egg contents using traditional candling methods, thus limiting management options. This paper tests a novel method of preparing thick‐shelled or opaque eggs so that traditional egg candling and blood extraction methods may be applied. Eggs from captive emu ( Dromaius novaehollandiae, Latham 1790) and southern cassowary ( Casuarius casuarius johnsonii, Linnaeus 1758) were obtained, and partial fenestration was performed on two areas of shell either before incubation or at ⅓ of incubation. Hatchability and weight loss were examined as a measure of effect of the fenestration process on the developing embryo. Clear observation of vascular development was successful in 97% of viable fenestrated eggs, without affecting hatchability or weight loss. Blood samples were taken from developing embryos and DNA was successfully extracted for proof of concept of this new technique. The ability to observe vascular development and monitor the developing embryo in thick and opaque eggs will significantly improve both in situ and ex situ population management options such as in ovo sexing in species of concern. Abstract : Research problem: Thick and opaque egg shells prevent the observation of an embryos vascular system upon candling; a precursor for blood extraction and follow‐up analysis. Solution: Fenestration of two sites on the shell surface promote visibility of egg contents without harmful effects on the embryo. Research Highlights: 1. The fenestration of two sites on the shell surface extends the use of traditional candling methods to thick and opaque eggs, without harmful effects on the embryo. 2. Early observation of the vascular system in thick and opaque eggs facilitates additional reproductive technologies and improves management options.